2010
DOI: 10.1186/1465-9921-11-145
|View full text |Cite
|
Sign up to set email alerts
|

DMF inhibits PDGF-BB induced airway smooth muscle cell proliferation through induction of heme-oxygenase-1

Abstract: BackgroundAirway wall remodelling is an important pathology of asthma. Growth factor induced airway smooth muscle cell (ASMC) proliferation is thought to be the major cause of airway wall thickening in asthma. Earlier we reported that Dimethylfumarate (DMF) inhibits platelet-derived growth factor (PDGF)-BB induced mitogen and stress activated kinase (MSK)-1 and CREB activity as well as IL-6 secretion by ASMC. In addition, DMF altered intracellular glutathione levels and thereby reduced proliferation of other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Glutathione ethylester (GSH-OEt) was dissolved to a final concentration of 1 mM in serum-free medium. The cytotoxic efficacy of DMF concentrations was not significant, as reported previously [13].…”
Section: Drug Preparationsupporting
confidence: 85%
See 3 more Smart Citations
“…Glutathione ethylester (GSH-OEt) was dissolved to a final concentration of 1 mM in serum-free medium. The cytotoxic efficacy of DMF concentrations was not significant, as reported previously [13].…”
Section: Drug Preparationsupporting
confidence: 85%
“…Previously, we reported that DMF significantly reduces the PDGF-BB-induced proliferation of ASMCs through induction of HO-1, suggesting that DMF may reduce airway remodelling [13]. In this study, we were interested in whether DMF-mediated up-regulation of HO-1 is also involved in DMF's anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, it has been demonstrated that a chemical that depletes GSH induced HO-1 by activation of p38 MAPK in airway smooth muscle cells (33). In addition, EP has also been shown to deplete GSH in LPS-stimulated RAW 264.7 cells (36).…”
Section: Ep Depletes Gsh and Activates P38 Mapk And Nrf2 In Lps-activmentioning
confidence: 99%